A MUSE inquiry into the physical processes taking place within the Abell 2667 Brightest Cluster Galaxy. Issue Volume 15:Issue S341(2019) (November 2019) - Iani, E.; Rodighiero, G.; Fritz, J.; Cresci, G.; Mancini, C.; Tozzi, P.; Rodríguez-Muñoz, L.; Rosati, P.; Caminha, G. B.; Berta, S.; Cassata, P.; Concas, A.; et al.
Abstract: Brightest cluster galaxies (BCGs) residing in cool-core clusters are known to be the stage of intricate baryon cycle phenomena (e.g. gas inflows, AGN outflows, star formation feedback). The scenarios describing the observed properties of these galaxies are still controversial, suffering from limitations due to the spatial resolving power of the instruments, specifically for galaxies beyond the Local Universe. However, the dramatic improvements introduced by the integral-field unit instruments (e.g. MUSE) could shed light on the physical processes driving the evolution of these galaxies. We present an extensive analysis of the stellar and gas properties (i.e. kinematics, stellar mass, star formation rate) of the radio-loud BCG sitting at the centre of the X-ray luminous cool-core cluster Abell 2667 ( z = 0.23), based on MUSE data. Our results indicate that the BCG is a massive elliptical, hosting an AGN that is possibly undergoing accretion of cold star-forming clouds of ICM or galactic cannibalism.